2021
DOI: 10.1111/tbed.14332
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the proximity to nomadic travel routes and environmental factors on the occurrence of cutaneous leishmaniasis in Kohgiluyeh and Boyer–Ahmad province, southwestern Iran

Abstract: Cutaneous leishmaniasis (CL) is one of the most important health challenges in hyperendemic countries like Iran. Geospatial information systems-based studies have shown that factors, including land cover, altitude, slope temperature, rainfall and animal livestock, affect CL distribution in Kohgyloyeh and Boyerahmad province, southwestern Iran. However, the question of the influence of nomadic tribes, who travel with their goats and sheep, on CL is unanswered. We, therefore, investigated their role in CL epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Therefore, the abundance of sand fly population close to human settlements can increase the risk of disease. The result of our study was consistent with other studies that reported a notable number of leishmaniasis patients to work or have been on agricultural farms (36)(37)(38)(39). However, the investigation conducted by Mokhtari et al (40) in Ilam demonstrated that the development of irrigation for agricultural aims in an arid area significantly decreased ZCL cases.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the abundance of sand fly population close to human settlements can increase the risk of disease. The result of our study was consistent with other studies that reported a notable number of leishmaniasis patients to work or have been on agricultural farms (36)(37)(38)(39). However, the investigation conducted by Mokhtari et al (40) in Ilam demonstrated that the development of irrigation for agricultural aims in an arid area significantly decreased ZCL cases.…”
Section: Discussionsupporting
confidence: 92%